Telomeres, telomerase, and cancer: mechanisms, biomarkers, and therapeutics - Songting Shou; Ayidana Maolan; Di Zhang; Xiaochen Jiang; Fudong Liu; Yi Li; Xiyuan Zhang; En Geer; Zhenqing Pu; Baojin Hua; Qiujun Guo; Xing Zhang; et al. (Experimental Hematology & Oncology)
Abstract Telomeres and telomerase play crucial roles in the initiation and progression of cancer. As biomarkers, they aid in distinguishing benign from malignant tissues. Despite the promising therapeutic potential of targeting telomeres and telomerase for therapy, translating this concept from the laboratory to the clinic remains challenging. Many candidate drugs remain in the experimental stage, with only a few advancing to clinical trials. This review explores the relationship between telomeres, telomerase, and cancer, synthesizing their roles as biomarkers and reviewing the outcomes of completed trials. We propose that changes in telomere length and telomerase activity can be used to stratify cancer stages. Furthermore, we suggest that differential expression of telomere and telomerase components at the subcellular level holds promise as a biomarker. From a therapeutic standpoint, combining telomerase-targeted therapies with drugs that mitigate the adverse effects of telomerase inhibition may offer a viable strategy.